Artificial Intelligence in 21st century education: an exploration of Its implementation, benefits, challenges, and ethical consequences - Quezada Vera, Cristian (2025)
The present article explores and analyzes the educational benefits, professional challenges,and ethical consequences of implementing artificial intelligence in the current educationalcontext. It seeks to understand how artificial intelligence has won space like an innovativeeducational resource both inside and outside the classroom; starting from assisting teachersand students, supporting learning processes, and the leadership of educational actors in theuse of this technology. For this reason, this research proposes a qualitative methodology ofdocument analysis and diagnostic of artificial intelligence software that can help andcontribute to the teaching-learning process. The analysis of concepts and theories related toartificial intelligence, as well like specialized programs of this type of technology applied inthe educational context, allowed understanding of the benefits and challenges, how to help inthe planning processes and assist teachers with educational needs, or support in the resolutionof learning problems in students. It also determines some of the ethical consequences of itsuse and application in the processes of knowledge transmission and construction, promotingthe proper and moderate use of this technology without falling into dependency on it,especially in today's world where technologies like the Internet have changed the wayeducation is conducted, hence the importance of analyzing and exploring the use of artificialintelligence in education.